From technology race to technology marathon: A behavioral explanation of technology advancement. Issue 2 (April 2017) - Wang, I. Kim; Qian, Lihong; Lehrer, Mark
Abstract: In industries characterized by continual progress from lower to higher generations of technology, firms seek to solidify their competitive position by deploying technologies more advanced than their current ones. This study attempts to provide behavioral explanations for the degree of technology advancement pursued by a firm. Using data from the flat panel display industry, we find that the extent of a firm's technology advancement is largely determined by how far it falls below the industry average. Our findings complement prior research on technology races by suggesting that firms in the thin-film-transistor liquid-crystal display (TFT-LCD) industry largely attempt to run a "marathon" rather than a sprint: the degree of technology advancement is mainly guided by a desire not to fall behind the pack as opposed to trying to move ahead of the pack in order to win the race. By the same token, firms exceeding the industry average in their technology reveal little motivation even to maintain their lead, much less extend it.